Pemberdayaan Anggota PKK Kelurahan Punggawan Kota Surakarta Melalui Workshop Lilin Aromaterapi dari Minyak Jelantah - Salsabila, Alifia Salmaa; Setyaningsih, Arinda Oktariski; Lusiana, Friska; Putri, Gita Indah Purnama; Musyafa, Irfan; Rohmah, Nafi Satur; Destiana, Risa Tri; Putra, Rheza Alexa; Nurni, Talitha Amalia; Mufidah, Zahrotul; Estriyanto, Yuyun (FKIP Universitas Sebelas Maret, 2024)
The use of cooking oil in daily life continues to increase over time. The large use of cooking oil causes an abundance of used cooking oil (cooking oil waste) and will have negative impacts if it is not processed properly. In fact, the facts on the ground show that used cooking oil has not been widely used by the community in several areas, including the community in Punggawan Village. Based on this problem, one of the 2023 UNS KKN teams conducted a workshop on making aromatherapy candles. The aim of this workshop activity is to utilize used cooking oil waste into useful products in the Punggawan Village community. The methods used are socialization and direct practice. This activity is divided into three stages, namely: (1) planning and preparation; (2) implementation of activities; and (3) program follow-up. This planning and preparation stage requires coordination with the PKK as well as preparing the tools and materials that will be used. The activity consists of presenting material and direct practice in making aromatherapy candles. The follow-up stage of this program is that the community is able to reduce and utilize used cooking oil waste. This workshop activity was attended by 30 participants who came from PKK members in Punggawan Village, Banjarsari District, Surakarta City. The results of this activity show that there is positive feedback from participants who participated actively during the workshop. This activity is expected to provide knowledge and experience for PKK members so they can utilize used cooking oil waste to process it into products that are useful and have sales value.